(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Phishing is a type of social engineering where an attacker sends a fraudulent message designed to trick a human victim into revealing sensitive information to the attacker or to deploy malicious software on the victim’s infrastructure like ransomware. Phishing attacks have become increasingly sophisticated and often transparently mirror the site being targeted, allowing the attacker to observe everything while the victim is navigating the site, and transverse any additional security boundaries with the victim. Now-a-days most of the people were familiar with the internet and its applications. Along with the internet usage, the attacks also have increased. Phishing is the one the most possible attacks in internet and through this the Phisher will get the confidential information like passwords. So that the users will not be able to access their own information. In this paper, an overview of phishing its techniques and anti-phishing methods are discussed.